The Evaluation of English Textbook for Ninth Grade Students of Junior High School Entitled: Bahasa Inggris: “Think Globally Act Locally” - Anjela Wela; Susilawati Endang; Surmiyati Surmiyati (CV. Publikasi Indonesia, 2025)
This research intended to determine the components of the scientific approach included in learning activities of the English textbook entitled Bahasa Inggris